The Use of Biomarkers for Bladder Cancer Diagnosis and Surveillance - Grubmüller, Bernhard; Roupret, Morgan; Briganti, Alberto; F. Shariat, Shahrokh (Mini Reviews in Medicinal Chemistry, 2016)
Bladder cancer - a propensity that is associated with high recurrence and mortality rates. Various molecular alterations are reflected by diverse cellular morphological manifestations and vast tumor heterogeneity. Many biomarkers have been described that have undergone clinical trials and are approved for clinical use, but most still remain investigational. The question how molecular markers can support surveillance of different patient groups is still a matter of controversy. However, it can be expected that major advancement in the understanding of molecular pathways involved in urothelial carcinogenesis will enable improved patient management. The scope of this review is to discuss the established diagnostic tests and urinary biomarkers and their application for screening and surveillance of bladder cancer.
Keywords: Cytology